Experimental investigation of a process chain combining sheet metal bending and laser beam melting of Ti-6Al-4V - Butzhammer, Lorenz; Dubjella, Patrick; Huber, Florian; Schaub, Adam; Aumüller, Markus; Baum, Alexander; Petrunenko, Oleksandra; Merklein, Marion; Schmidt, Michael (Lasers in Manufacturing LIM 2017, 2017)
In spite of several advantages such as a great freedom of design, comparatively long process times are a major drawback in additive manufacturing technologies such as laser beam melting (LBM) of metal powder. A strategy to overcome this limitation is to combine additive manufacturing with other promising manufacturing concepts. In this paper, we characterize hybrid components manufactured using a consecutive process chain including warm bending of Ti-6Al-4V sheets and LBM. With the additive process a functional structure is built on top of the bending zone using powder from the same material. As a measure for the connection strength, shear tests were performed. The shear strength is analyzed for both possible process routes of forming and LBM. Therefore a modular clamping device for bent sheets was developed in order to enable simultaneous production of additive parts on several bent sheets with different thicknesses and radii. Results show that the formability of sheets is strongly influenced by the sequence of the process route, while no significant difference in shear strength of the connection was observed, even if the energy density in the LBM process is varied to a large extent. The post heat treatment is discussed as major cause, as homogenization of the microstructure takes place, although the applied temperature is beneath the beta transus temperature.
Keywords: Laser Beam Melting; Additive Manufacturing; Bending; Titanium Alloys

Influence of a bending operation on the bonding strength for hybrid parts made of Ti-6Al-4V - Papke, Thomas; Dubjella, Patrick; Butzhammer, Lorenz; Huber, Florian; Petrunenko, Oleksandra; Klose, Dominik; Schmidt, Michael; Merklein, Marion (Procedia CIRP, 2018)